Evidence for the Cytoplasmic Localization of the L-α-Glycerophosphate Oxidase in Members of the “Mycoplasma mycoides Cluster” - Schumacher, Melanie; Nicholson, Pamela; Stoffel, Michael H.; Chandran, Suchismita; D’Mello, Adonis; Ma, Li; Vashee, Sanjay; Jores, Joerg; Labroussaa, Fabien (Frontiers in Microbiology, 2019)
Members of the ‘Mycoplasma mycoides cluster’ are important animal pathogens causing diseases including contagious bovine pleuropneumonia and contagious caprine pleuropneumonia, which are of utmost importance in Africa or Asia. Even if all existing vaccines have shortcomings, vaccination of herds is still considered the best way to fight mycoplasma diseases, especially with the recent and dramatic increase of antimicrobial resistance observed in many mycoplasma species. A new generation of vaccines will benefit from a better understanding of the pathogenesis of mycoplasmas, which is very patchy up to now. In particular, surface-exposed virulence traits are likely to induce a protective immune response when formulated in a vaccine. The candidate virulence factor L-α-glycerophosphate oxidase (GlpO), shared by many mycoplasmas including Mycoplasma pneumoniae, was suggested to be a surface-exposed enzyme in Mycoplasma mycoides subsp. mycoides responsible for the production of hydrogen peroxide directly into the host cells. We produced a glpO isogenic mutant GM12::YCpMmyc1.1-ΔglpO using in-yeast synthetic genomics tools including the tandem-repeat endonuclease cleavage (TREC) technique followed by the back-transplantation of the engineered genome into a mycoplasma recipient cell. GlpO localization in the mutant and its parental strain was assessed using scanning electron microscopy (SEM). We obtained conflicting results and this led us to re-evaluate the localization of GlpO using a combination of in silico and in vitro techniques, such as Triton X-114 fractionation or tryptic shaving followed by immunoblotting. Our in vitro results unambiguously support the finding that GlpO is a cytoplasmic protein throughout the ‘Mycoplasma mycoides cluster’. Thus, the use of GlpO as a candidate vaccine antigen is unlikely to induce a protective immune response.